ANALISIS PERMINTAAN KEDELAI DI INDONESIA - Pusposari, Luthfiya Fathi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Indonesian population growth from year to year has increased, the population of Indonesia has incense for about 20 million people from the previous census data. Soybean is one of commodity most consumed by society census. Demand of soybean in this country 2,4 million tons per year, as much as 70% comes from imported soybean. Based on demand theory there are many factors that influence demand of goods, among others, the price of the goods themselves, the price of other goods, population, etc. Purpose of this research is to understand the elasticity of Â soybeanâ€™s demand in East Java and what variable which have the highest elasticity. The result of this research shows that variable of soybean's price is in elastic towards demand of soybean while variable of corn's price, income per capita and population is elastic. Variable which has sensitivity or the highest elasticity is variable of populationKeyword: Demand, Elasticity, Soybean